Hearing Preservation up to 3 Years After Gamma Knife Radiosurgery for Gardner-Robertson Class I Patients With Vestibular Schwannomas. Issue 5 (19th February 2015) - Mousavi, Seyed H.; Kano, Hideyuki; Faraji, Amir H.; Gande, Abhiram; Flickinger, John C.; Niranjan, Ajay; Monaco, Edward; Lunsford, L. Dade
Abstract: BACKGROUND: Vestibular schwannoma patients with Gardner-Robertson (GR) class I hearing seek to maintain high-level hearing whenever possible. OBJECTIVE: To evaluate hearing outcomes at 2 to 3 years in GR class I patients who underwent Gamma Knife radiosurgery (GKRS). METHODS: Sixty-eight patients with GR class I hearing were identified between 2006 and 2009. Twenty-five patients had no subjective hearing loss (group A) and 43 patients reported subjective hearing loss (group B) before GKRS. The median tumor volume (1 cm 3 ) and tumor margin dose (12.5 Gy) were the same in both groups. RESULTS: Serviceable hearing retention rates (GR grade I or II) were 100% for group A compared with 81% at 1 year, 60% at 2 years, and 57% at 3 years after GKRS for group B patients. Group A patients had significantly higher rates of hearing preservation in either GR class I ( P < .001) or GR class II ( P < .001). Patients with a pure tone average (PTA) <15 dB before GKRS had significantly higher rates of preservation of GR class I or II hearing. CONCLUSION: At 2 to 3 years after GKRS, patients without subjective hearing loss or a PTA <15 dB had higher rates of grade I or II hearing preservation. Modification of the GR hearing classification into 2 groups of grade I hearing (group A, those with no subjective hearing loss and a PTA <15 dB; and group B, those with subjective hearing loss and a PTA >15 dB) may be useful to help predict hearing preservation rates at 2 to 3 years after GKRS.